Dari Sampah Jadi Rupiah: Pemberdayaan Ekonomi Warga Melalui Revitalisasi Manajemen Bank Sampah - Lutfi Ariefianto; AT Hendrawijaya; Muhammad Irfan Hilmi; Linda Fajarwati (Jurnal Nusantara Berbakti, 2026)
Suboptimal waste management has become a serious problem in local communities, even though inorganic waste has high economic potential if managed wisely. In Tegalsari Village, Ambulu Subdistrict, waste management needs to be strengthened through a financial approach. This community service activity aims to empower the economy of Tegalsari Village residents by revitalizing the management of the waste bank so that it provides direct economic value that can increase household income. The implementation of this activity was carried out through a planning phase that included program coordination meetings, the formation and revitalization of the management structure, educational outreach on the economic value of waste, and a partnership collaboration with the Karya Mandiri Jember Central Waste Bank (BSI). Furthermore, the operational implementation phase includes the sorting of inorganic waste by residents in their respective homes, weighing, recording financial transactions in customer savings books, and transporting the waste to collectors. The results of these activities demonstrate the establishment of a more organized management system and an increase in residents’ active participation in waste sorting. The profit-sharing system for customer savings from waste sales has proven effective in boosting residents’ enthusiasm, enabling the program to tangibly transform waste into income while strengthening the domestic economic resilience of the Tegalsari Village community.